Analyzing the existing programs on promoting women scientists in chemistry - Fung Fun Man; Markic Silvija; Mamlok-Naaman Rachel; Cesa Mark; Chiu Mei-Hung (Chemistry Teacher International, 2024)
Gender imbalance in science has been well documented. Possible explanations include a lack of systematic strategies or policies to support women in science in general and chemistry in particular. This article aims to analyze selected programs that advocate gender equity and inclusion in chemistry. Forty-eight initiatives were selected via several steps of screening. Following a pilot study using systematic review as a research method, the named initiatives were analyzed considering their strategies, goals, and impact. The findings reveal that acknowledging women scientists and providing funding to enable and sustain networking (such as through conferences) are crucial for women scientists to become visible and recognized in academia. In this paper, we offer recommendations for other entities who would like to develop initiatives to encourage suitable environments for gender equity.